2017
DOI: 10.1063/1.4975040
|View full text |Cite
|
Sign up to set email alerts
|

Raman study of the vibrational modes in ZnGeN2 (0001)

Abstract: A Raman spectroscopy study was carried out for ZnGeN2 with direction of propagation along the (0001) crystallographic direction on hexagonal single crystal platelets obtained by reaction of gaseous ammonia with a Zn-Ge-Sn liquid alloy at 758 • C. The sample geometry allowed measurement of the a2 and a1 Raman modes. First-principles calculations were carried out of the spectra. Measurements with crossed polarizers yielded spectra that agreed well with first-principles calculations of the a2 modes. Measurements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, the relatively low temperature of 250 °C can limit the potential to obtain a perfectly ordered crystal. Sharp, well-defined Raman peaks have been observed from crystalline ZnGeN 2 needles and platelets grown at 750 °C and higher temperatures 18 , 19 , 25 , 26 , suggesting that higher cation ordering might be achieved through the MBE growth of ZnSn x Ge 1−x N 2 samples at higher temperatures than used herein, if thermal expansion coefficients allow for such on suitable substrates. Investigations utilizing higher temperature growth may reduce point defects and strain, with enhancement of optoelectronic properties, and enable the development of material suitable for use in high-performance devices.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the relatively low temperature of 250 °C can limit the potential to obtain a perfectly ordered crystal. Sharp, well-defined Raman peaks have been observed from crystalline ZnGeN 2 needles and platelets grown at 750 °C and higher temperatures 18 , 19 , 25 , 26 , suggesting that higher cation ordering might be achieved through the MBE growth of ZnSn x Ge 1−x N 2 samples at higher temperatures than used herein, if thermal expansion coefficients allow for such on suitable substrates. Investigations utilizing higher temperature growth may reduce point defects and strain, with enhancement of optoelectronic properties, and enable the development of material suitable for use in high-performance devices.…”
Section: Introductionmentioning
confidence: 80%
“…The broad ZnSn x Ge 1−x N 2 peaks indicate that the bond vibrations probed are not well ordered, representing non-periodicity in the lattice 16 that may result from random cation positioning 17 19 . Studies of plasma-assisted vapor-liquid-solid growth of ZnSnN 2 at 485 °C resulted in similarly broad Raman peaks, with the broad peaks attributed to imperfect lattice ordering 16 such as cation anti-site defects 18 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently we also studied BeGeN 2 and BeSiN 2 's electronic band structure and phonons . BeSiN 2 has been synthesized and its band structure was previously studied at the LDA level by Shaposhnikov et al and Huang et al Experimental studies of the Raman spectra have been reported for ZnGeN 2 , and an infrared study of the phonons in ZnSiN 2 was reported by Mintairov et al and analyzed somewhat differently in ref. .…”
Section: Literature Reviewmentioning
confidence: 98%
“…MOCVD growth of (ZnGe) 1−x Ga 2x N 2 thin films on c-and r-plane sapphire as well as GaN/c-sapphire was also reported [19]. Experimental investigations of ZnGeN 2 have mainly focused on the morphological [5,[16][17][18][19], optical [3,5,16,17,20], crystal structural [5,7,[16][17][18][19][20][21], and lattice vibrational properties [21][22][23]. Deeplevel defects in MOCVD-grown ZnGeN 2 films on sapphire substrates have also been investigated [24].…”
Section: Introductionmentioning
confidence: 99%